PRIORITY RANKING OF SOCIAL SYSTEMS IN MANAGING THE SOCIO-CULTURAL PROCESSES: PUBLIC OPINION - Sagitov, Salavat; Nasibullin, Ravil; Bakhtizin, Ramil (Revista Inclusiones, 2020)
The paper presents the results of a sociological study of the contradictions in the management system in culture. The aim of the study is to identify the characteristics of the perception of problems of various social groups existing in the modern management system in culture. The main method for this work is a longitudinal sociological research allowing to identify trends in cultural management processes in course of a certain period. The results were obtained by the authors of sociological research in the field of culture in the Republic of Bashkortostan in 2001-2002 and 2016-2017 in the form of a questionnaire survey of 2400 respondents. It was revealed that in the early XXI century, the majority of respondents believed that the culture development issues should be mainly coped with at the regional level (46%), while the federal level was given just over a fifth of the votes. Currently less than one third of the respondents prefer the regional level, and almost half - of the federal (47%). Conclusion: there occur an active transformation of ideas about the structural elements of the management system and their correlation; the public opinion about levels of management in the sphere of culture, which has important theoretical and practical significance, is also changing.